2016
DOI: 10.20914/2310-1202-2016-2-148-152
|View full text |Cite
|
Sign up to set email alerts
|

The fermented milk product of functional destination

Abstract: 1 кафедра технологии продуктов животного происхождения, Воронеж. гос. ун-т инж. техн., пр. Революции, 19, Воронеж, 394036, Россия Реферат. В качестве вкусового компонента выбран сироп, приготовленный из калины. Эта ягода широко используется в разных формах в пищевой промышленности, в том числе и молочной. Особое внимание следует обратить на то, что калина является дикорастущим растением, и не требует затрат на посадку и культивирование. Калина богата биологически активными веществами и является лекарственным с… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
0
8
0
3
Order By: Relevance
“…According to the literature, Maksimenko et al (2014), Zhbanova & Maslennikov (2015), organic acids in ripe fruits of snowball tree are represented mainly by malic, citric, caprylic, formic, valeric, isovaleric, chlorogenic acids, and also traces of quinic, caffeic and acetic acids were detected. Savieliev et al (2010), Golubieva et al (2016), Zhidekhina et al (2016 reported that green fruits (unlike ripe fruits) are rich in quinic and caffeic acids, the content of which significantly reduces during ripening. Ersoy et al (2017), Goszcz et al (2017), Cory et al (2018), Kızılay (2019) found that the fruits of the snowball tree contain triterpene compounds: α-and β-amyrin, alanolic and hedrogenic acids and their acetyl derivatives, ursolic acid, as well as steroids represented by phytosterol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature, Maksimenko et al (2014), Zhbanova & Maslennikov (2015), organic acids in ripe fruits of snowball tree are represented mainly by malic, citric, caprylic, formic, valeric, isovaleric, chlorogenic acids, and also traces of quinic, caffeic and acetic acids were detected. Savieliev et al (2010), Golubieva et al (2016), Zhidekhina et al (2016 reported that green fruits (unlike ripe fruits) are rich in quinic and caffeic acids, the content of which significantly reduces during ripening. Ersoy et al (2017), Goszcz et al (2017), Cory et al (2018), Kızılay (2019) found that the fruits of the snowball tree contain triterpene compounds: α-and β-amyrin, alanolic and hedrogenic acids and their acetyl derivatives, ursolic acid, as well as steroids represented by phytosterol.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative source of many components of nutrition are fruit plants, in particular, rowan Sorbus aucuparia L., aronia Aronia melanocarpa (Michx.) Elliott, amelanchier Amelanchier canadensis (L.) Medik., sea buckthorn Hippophae rhamnoides L., quince Cydonia oblonga Mill., snowball tree Viburnum opulus L., dogwood Cornus mas L. and others (Golubieva et al, 2016;Sіzaуа et al, 2017;Moskalets et al, 2019). Their raw materials are a source of vitamins, minerals, dietary fiber and other vital nutrients, necessary for normal metabolic processes in the human body (Skrovankova et al, 2015;Jurikova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Как известно, свободные аминокислоты легко всасываются через кишечную стенку и активно используется организмом человека на свои нужды. Поэтому внесение ГСБ не только повышает общее содержание белка, но и существенно улучшает биологическую ценность готового продукта [2]. ГСБ прошел клинические испытания в медицинских учреждениях для лечения и реабилитации больных с различной степенью белково-энергетической недостаточности.…”
unclassified